Flies as possible vectors of inflammatory trachoma transmission in a brazilian municipality - Meneghim, Roberta Lilian Fernandes de Sousa [UNESP]; Madeira, Newton Goulart [UNESP]; Ribolla, Paulo Eduardo Martins [UNESP]; Padovani, Carlos Roberto [UNESP]; Schellini, Silvana Artioli [UNESP] (FapUNIFESP (SciELO), 2021)
Trachoma is a keratoconjunctivitis caused by Chlamydia trachomatis, considered an important leading cause of preventable blindness in the world. This study aimed at verifying if flies can be the vectors for trachoma in our municipality. Flies were assessed in the households of children diagnosed with inflammatory trachoma at the municipality of Botucatu, Sao Paulo State, Brazil. Fly traps were placed in the backyard of the houses during 24 h, in each of the four weather seasons, over a period of one year. The collected dipterans were taxonomically classified and the presence of Chlamydia trachomatis in the flies was evidenced by using the Polymerase Chain Reaction (PCR). During the studied period, 2,188 flies were collected, mainly during the summer and the spring. The most common identified fly was Musca domestica. All fly samples were negative for Chlamydia trachomatis but several other different bacteria were identified in these flies. The authors concluded that flies are probably not the vectors for trachoma in the studied area. Further studies should be conducted to evaluate other possible factors responsible for the maintenance of the disease in our environment.
Keywords: Chlamydia trachomatis; Classification; Houseflies; Polymerase-chain reaction; Tachoma; Vectors